Analisis Gaya Belajar Ditinjau dari Hasil Belajar Siswa - Frita Devi Asriyanti; Lilis Arinatul Janah (Faculty of Education Universitas Negeri Malang, 2018)
Abstract: Learning style is the way that every individual receives learning and information from his environment. Learning outcomes are the number of students who have different intelligence, namely the ability of students to do the given questions, with the same values as when learning learning takes place. The formulation of the problem in this study is the kinds of learning styles that are displayed from the learning outcomes of fifth grade students and how is the analysis of learning styles learned from the learning outcomes of Class V students at Pagersari I Elementary School 2017/2018 Academic Year. This research method uses knowledge list data, questionnaires, interviews and documentation. This method is used to obtain data from learning style variables and student learning outcomes. The results of data research obtained by the average student learning style is visual or learning style by way of seeing. From the learning outcomes of students obtained in the cognitive domain that is on the values of students when working on the questions given by the teacher during the process of teaching and learning takes place. The results of this study can be used to study learning styles on student learning outcomes and can be at SDN Pagerari I for schools and parents to overcome problems in Class V. Abstrak: Gaya belajar adalah suatu cara yang dilakukan oleh setiap individu dalam menerima pelajaran dan informasi dari lingkungannya. Hasil belajar adalah sejumlah pengalaman yang diperoleh siswa yang mencakup ranah kognitif adalah kemampuan siswa dalam mengerjakan soal yang diberikan. Rumusan masalah pada penelitian ini apakah macam-macam gaya belajar ditinjau dari hasil belajar siswa dan bagaimanakah analisis gaya belajar ditinjau dari hasil belajar siswa Kelas V di SDN Pagersari I tahun pelajaran 2017/2018. Metode penelitian ini menggunakan pengumpulan data berupa observasi, angket, wawancara dan dokumentasi. Metode ini digunakan untuk memperoleh data dari variabel gaya belajar dan hasil belajar siswa. Hasil analisis diperoleh data rata-rata gaya belajar siswa adalah visual atau gaya belajar dengan cara melihat. Dari analisis hasil belajar siswa diperoleh pada ranah kognitif yaitu pada nilai evaluasi siswa pada saat mengerjakan soal evaluasi yang diberikan oleh guru saat proses kegiatan belajar mengajar berlangsung. Hasil penelitian ini dapat digunakan untuk mengetahui gaya belajar terhadap hasil belajar siswa serta dapat digunakan SDN Pagersari I untuk pertimbangan sekolah serta orang tua siswa untuk memperbaiki perhatian kepada siswa terutama yang berada di Kelas V.